MFCC dan KNN untuk Pengenalan Suara Artikulasi P - Akhmad Anggoro; Samiadji Herdjunanto; Risanuri Hidayat (Aviation Electronics, Information Technology, Telecommunications, Electricals, Controls (AVITEC), 2020)
Cleft lip and palate (CLP) is a term for patients who experience speech organ disorders, that disorder is caused by a gap found in the lip or palate. Patients will experience speech problems. Pattern recognition in CLP sound is still small in Indonesia. In this research in the language identification of CLP and standard sound patterns using the extraction of the Mel Frequency Cepstral Coefficients (MFCC) feature with K-Nearest Neighbor (KNN) classification and K-Fold cross-validation. By making words that have the letter /p/ as a reference, known as bilabial. The words used include Paku, Kapak, and Atap. The accuracy of recognition results reached more than 69%, with a minimum accuracy of 41%.